LINGKUNGAN KELUARGA DENGAN PERKEMBANGAN PSIKOSOSIAL ANAK USIA PRASEKOLAH DI TK SRIKANDI KECAMATAN TELAGA BIRU KABUPATEN GORONTALO - Firmawati Firmawati; Nur Uyuun I. Biahimo; Sriwahyuni Y Djukisana (Zaitun (Jurnal Ilmu Kesehatan), 2020)
The family environment is the first and foremost aspect in influencing the development of children. At preschool age, children's psychosocial development is obvious, because they have begun to actively relate to their peers. The aim of the research was to determine the relationship between family environment and psychosocial development of preschool children at TK Srikandi, Telaga Biru Sub district, Pentadio Timur Village, Gorontalo District. The design is descriptive quantitative using a cross sectional study approach. From the results obtained a value of p value = 0.012 which means it is smaller than α = 0.05 (Chi square Test). Therefore it was concluded that there was a correlation between the family environment and psychosocial development of preschoolers at Srikandi Kindergarten in Pentadio Timur. Based on these results, the researcher suggest that TK should conduct learning that involves parents directly at certain events, so parents are actively involved in the child's learning process.